Association between carbohydrate quality and glycemic control in individuals with type 1 diabetes: A cross-sectional and meal-based analysis - Lingling Bian; Chun Yang; Yanjun Jin; Hong Wang; Min Zhu; Jingjing Xu; Jianling Bai; Mei Zhang; Yanmei Liu; Tao Yang; Yong Gu; Hechun Liu (PLoS ONE, 2026)
The aim of the study was to investigate the association between the quality of carbohydrates in the diet and glycemic control in individuals with Type 1 Diabetes (T1D). In this cross-sectional study, a dietary survey involving 155 individuals with T1D used a food frequency questionnaire (FFQ) and 3-day dietary records from 65 individuals to analyze 538 meals. The relationship between short-term dietary factors and postprandial glycemic fluctuations was evaluated by a mixed-effects model. The FFQ survey indicated that a higher intake of dietary fiber was associated with better long-term glycemic control (HbA1c≤6.5%) in T1D individuals (OR=1.101, p = 0.031). Analysis of 3-day dietary records and continuous glucose monitoring (CGM) data showed an inverse correlation between whole grain intake and postprandial glycemic variability, measured by standard deviation (SD), large amplitude of glycemic excursions (LAGE) and mean amplitude of glycemic excursions (MAGE) (Est. = −0.83, p < 0.01; Est. = −2.4, p < 0.01; Est. = −1.47, p = 0.04). Specifically, blood glucose fluctuations (SD, LAGE, MAGE) were more significant after lunch (p < 0.05), and these fluctuations were negatively related to the intake of whole grains (Est. = −0.45, p = 0.02; Est. = −1.52, p = 0.01; Est. = −1.39, p < 0.01). From a long-term glycemic control perspective, higher dietary fiber intake appears to be associated with improved HbA1c levels, while in terms of short-term glycemic variability, increased whole grain consumption is associated with reduced glucose fluctuations. However, as a cross-sectional analysis, these findings represent observational associations rather than causal evidence. Further validation through prospective cohorts and randomized trials is needed to assess clinical applicability.